Long term program development (LTPD): An interdisciplinary framework for developing athletes, coaches, and sport programs - Siwik, M.; Lambert, A.; Saylor, D.; Bertram, R.; Cocchiarella, C.; Gilbert, W. (International Sport Coaching Journal, 2015)
The purpose of this paper is to summarize a decade-long effort to create a replicable methodology for the design and sustainable development of educationally effective sport programs. Working at a macro level in parallel to the single-sport efforts of groups such as USA Hockey at the micro level, our goal has been to integrate existing and proven approaches from sport and other fields into an interdisciplinary framework that sport leaders and policymakers could use to address challenges such as declining youth enrollment, athlete retention, inadequate coach training, and fan avidity. The name we have chosen for the proposed framework is Long Term Program Development (LTPD). In the first section of the paper, we share the interdisciplinary foundation of LTPD. The second section provides an overview of the LTPD framework. Examples of the LTPD framework in action are presented in the third section. The fourth and final section sets forth our ideas about the future of LTPD and the anticipated roles of all levels of sport to further develop and disseminate LTPD. Finally, throughout the paper we highlight the need for sport leaders, including coaches, to approach their work as a teacher and servant leader, a core tenet of the LTPD framework.